Single-cell analysis identifies the CNP/GC-B/cGMP axis as marker and regulator of modulated VSMCs in atherosclerosis - Moritz Lehners; Hannes Schmidt; Maria T. K. Zaldivia; Daniel Stehle; Michael Krämer; Andreas Peter; Julia Adler; Robert Lukowski; Susanne Feil; Robert Feil (Nature Communications)
Abstract A balanced activity of cGMP signaling contributes to the maintenance of cardiovascular homeostasis. Vascular smooth muscle cells (VSMCs) can generate cGMP via three ligand-activated guanylyl cyclases, the NO-sensitive guanylyl cyclase, the atrial natriuretic peptide (ANP)-activated GC-A, and the C-type natriuretic peptide (CNP)-stimulated GC-B. Here, we study natriuretic peptide signaling in murine VSMCs and atherosclerotic lesions. Correlative profiling of pathway activity and VSMC phenotype at the single-cell level shows that phenotypic modulation of contractile VSMCs to chondrocyte-like plaque cells during atherogenesis is associated with a switch from ANP/GC‑A to CNP/GC‑B signaling. Silencing of the CNP/GC-B axis in VSMCs results in an increase of chondrocyte-like plaque cells. These findings indicate that the CNP/GC-B/cGMP pathway is a marker and atheroprotective regulator of modulated VSMCs, limiting their transition to chondrocyte-like cells. Overall, this study highlights the plasticity of cGMP signaling in VSMCs and suggests analogies between CNP-dependent remodeling of bone and blood vessels.